PENGARUH PERTUMBUHAN EKONOMI, PAD, DAU DAN DBH TERHADAP BELANJA DAERAH PROVINSI ACEH 2013-2017 - Malau, Yois Nelsari; Lase, Weni Listayani; Sagala, Vera Clodia Br; Lestari, Dedek (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2020)
The study aims to examine the effect of economic growth, local revenue, general allocation fund, and revenue sharing fund on regional expenditure in Aceh province of 2013-2017. Population and sample amounted to 23 districts/cities from 2013-2017, using saturated sampling techniques. Gained the coefficient of determination analysis was 0.864, meaning that the variable in regional expenditure were able to explain by variable economic growth, regional indigenous revenue, general allocation fund, and revenue share fund up to 86.4% and other free variables of 13,6%. The results of partial that economic growth, local revenue, and general allocation fund affect and significance, while revenue sharing fund is no affect on the regional expenditure. And simultaneously economic growth, local revenue, general allocation fund, and revenue sharing have an impact on the regional expenditure.